Differentially Expressed Genes Associated with Body Size Changes and Transposable Element Insertions between Caenorhabditis elegans and Its Sister Species, Caenorhabditis inopinata. (18th April 2023) - Kawahara, Kazuma; Inada, Taruho; Tanaka, Ryusei; Dayi, Mehmet; Makino, Takashi; Maruyama, Shinichiro; Kikuchi, Taisei; Sugimoto, Asako; Kawata, Masakado
Abstract: Why the recently discovered nematode Caenorhabditis inopinata differs so greatly from its sibling species Caenorhabditis elegans remains unknown. A previous study showed that C. inopinata has more transposable elements (TEs), sequences that replicate and move autonomously throughout the genome, potentially altering the expression of neighboring genes. In this study, we focused on how the body size of this species has evolved and whether TEs could affect the expression of genes related to species-specific traits such as body size. First, we compared gene expression levels between C. inopinata and C. elegans in the L4 larval and young adult stages—when growth rates differ most prominently between these species—to identify candidate genes contributing to their differences. The results showed that the expression levels of collagen genes were consistently higher in C. inopinata than in C. elegans and that some genes related to cell size were differentially expressed between the species. Then, we examined whether genes with TE insertions are differentially expressed between species. Indeed, the genes featuring C. inopinata -specific TE insertions had higher expression levels in C. inopinata than in C. elegans. These upregulated genes included those related to body size, suggesting that these genes could be candidates for artificial TE insertion to examine the role of TEs in the body size evolution of C. inopinata .